2005
DOI: 10.4049/jimmunol.174.11.7123
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal-Fetal Histocompatibility and MHC Zygosity on Maternal Microchimerism

Abstract: To investigate the relationship between maternal-fetal histocompatibility and maternal microchimerism, we developed a sensitive quantitative PCR assay for the neomycin resistance gene (neoR), and, in a mouse model system, used neoR as a noninherited maternal allele marker of maternal cells to detect and quantitate maternal microchimerism in tissues of neoR−/− N2 backcross progeny of (neoR+/−)F1 females mated with neoR−/− males. Using this approach, we obtained evidence for the presence of chimeric maternal cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 30 publications
(21 reference statements)
3
32
0
1
Order By: Relevance
“…Other possibilities include shared environmental factors as well as the possibility that a sibling may be more likely to share HLA and other genes with the mother than an unrelated individual. In a murine model, some histocompatibility relationships were found to correlate with increased levels of MMc (26). We were unable to explore this question because our methods were based on HLA incompatibility.…”
Section: Discussionmentioning
confidence: 98%
“…Other possibilities include shared environmental factors as well as the possibility that a sibling may be more likely to share HLA and other genes with the mother than an unrelated individual. In a murine model, some histocompatibility relationships were found to correlate with increased levels of MMc (26). We were unable to explore this question because our methods were based on HLA incompatibility.…”
Section: Discussionmentioning
confidence: 98%
“…In humans, maternal-fetal cellular trafficking may contribute to fetal immune development and maternal-fetal tolerance, inducing the fetus to develop Tregs against maternal antigens (19). Changes in the levels of maternal-fetal cellular trafficking have been reported to correspond with maternal-fetal histocompatibility in the mouse model, suggesting that cellular trafficking has implications for maternal-fetal tolerance (37,40).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that both in utero and oral exposure are required for the NIMA effect seen in this highly immunogenic murine heart allograft model (13). In utero exposure to maternal soluble Ags and cells, and the establishment of maternal microchimerism, could allow for NIMA presentation in the thymus, thus allowing for the development of natural T R cells (8,33,34). Oral administration of Ag has previously been shown to expand CD4 ϩ CD25 ϩ T R cells which are able to suppress DTH reactions (35), and under more physiological conditions like nursing, it has been shown that oral tolerance is largely mediated through mucosal induction of adaptive CD4 ϩ T R cells producing IL-10 and TGF-␤ that can suppress the systemic response to the same Ag (36,37).…”
Section: Discussionmentioning
confidence: 99%